Найдите значение выражения: -2(3,1х – 1) + 3(1,2х+1) – 8(0,3х+3) при х=0,8

Xtarlus Xtarlus    1   02.10.2019 06:30    1

Ответы
dimabashlik3857 dimabashlik3857  09.10.2020 11:09

-2(3,1х – 1) + 3(1,2х+1) – 8(0,3х+3)=

-6, 2х+2+3,6х+3-2,4х-24=-5х-19

-5*0,8-19=-4-19=-23

ПОКАЗАТЬ ОТВЕТЫ
petryskakate2003 petryskakate2003  09.10.2020 11:09

-2(3,1х – 1) + 3(1,2х+1) – 8(0,3х+3)=2-6,2х+3,6х+3-2,4х-24=-19-5х

Если х=0,8, то -19-5х=19-5*0,8=-19-4=-23

ответ:23

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика